Method for rapidly detecting content of residual flocculant in washing machine-made sand

Through the method of electron beam irradiation and critical moisture content difference measurement, the accuracy and efficiency of flocculant detection in water-washed sand is solved, and the rapid and accurate detection of flocculant content is achieved. It is suitable for a variety of flocculant and improves the Concrete pouring quality.

CN119198430APending Publication Date: 2024-12-27ANHUI RUIHE NEW MATERIALS CO LTD +1

Patent Information

Application Number
CN202411339252.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The prior art cannot quickly and accurately detect the residual flocculant content in the washed sand, resulting in poor concrete fluidity and loss of fluidity. Most methods are limited to polyacrylamide flocculants and are not suitable for other flocculants.

Method used

After the electron beam is used to irradiate the machine sand, the flocculant mass concentration is determined by measuring its critical moisture content difference, and a transparent tape scale round mold test mold and metal cylindrical tamping rod are used for uniform compaction and evaporation to avoid interference from the introduction of other materials. Improve the accuracy and repeatability of the detection.

Benefits of technology

It realizes rapid and accurate detection of the flocculant content in the washed sand, avoids interference from other materials, improves the accuracy and efficiency of detection, and is suitable for the detection of different flocculants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119198430A_ABST
    Figure CN119198430A_ABST
Patent Text Reader

Abstract

The invention discloses a method for rapidly detecting the content of a residual flocculating agent in washing machine-made sand, which comprises the following steps of: screening out particles with the particle size of more than 4.75 mm from machine-made sand to be detected, respectively testing the critical water contents of degraded and untreated machine-made sand samples, and determining the mass concentration range of the flocculating agent on the basis of the difference value of the critical water contents of the two kinds of machine-made sand. Compared with tests through neat paste, mortar and concrete systems, deviation possibly caused by introduction of other materials is avoided, and the method is more convenient, faster and more accurate. A'critical water absorption 'test method is provided according to the stability of the stacking state of sand, a transparent circular truncated cone test mold with scales is designed, the filling height and the tamping method of each layer of sample are accurately stipulated, and the test normalization and the test result repeatability of different time, different places and different operators are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a method for quickly detecting the residual flocculant content in water-washed machine-made sand. Background Art

[0002] In order to reduce the mud and powder content, the manufactured sand needs to be repeatedly washed with water during the water-washed sand treatment process. The water used to wash the manufactured sand cannot be reused many times because it contains a lot of mud, resulting in a huge amount of water consumption for washing the manufactured sand. The use of flocculants can effectively precipitate and recycle the wastewater after sand washing, thereby saving a lot of water. Among the many flocculants, polyacrylamide has a good effect of flocculating and precipitating impurities and purifying water quality, so it is widely used by machine-made sand manufacturers in the water washing process of machine-made sand. In addition, coagulants such as polyamines and polyaluminum chloride are also used in the treatment of machine-made sand. However, since the machine-made sand manufacturers add flocculants more arbitrarily during the production process, different amounts of flocculants remain in the machine-made sand, resulting in application problems such as poor concrete fluidity and large fluidity loss.

[0003] If the residual flocculant content in the washed machine-made sand is too high, it will have a negative impact on the concrete. Therefore, the flocculant content in the machine-made sand must be quickly detected and controlled to solve the impact of the flocculant on the concrete from the source. At present, the detection of residual flocculants in machine-made sand is mostly judged according to the working state of the mixture after the mortar and concrete system are mixed. Patent CN202311382158.5 determines the content of polyacrylamide flocculant in machine-made sand according to the fluidity range of mortar. CN202110861099.4 adds different concentrations of the flocculant to be tested into the concrete to obtain the influence of the flocculant to be tested on the working performance of the concrete and determine the qualified dosage standard of the flocculant to be tested. However, other raw materials are introduced into the mortar and concrete system, which has problems such as strong subjectivity and many interference factors. Moreover, most methods are limited to polyacrylamide flocculants and are not applicable to other flocculants.

[0004] Therefore, in order to ensure the quality of machine-made sand concrete pouring, it is urgent to develop a rapid and accurate detection method for the residual flocculant content in washed machine-made sand. Summary of the invention

[0005] In order to solve the shortcomings of the existing detection method of residual flocculant in machine-made sand, the purpose of the present invention is to provide a rapid detection method for the residual flocculant content in water-washed machine-made sand.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention is:

[0007] A method for quickly detecting the residual flocculant content in water-washed machine-made sand comprises the following steps:

[0008] Step 1: Screen the machine-made sand to be tested to remove particles larger than 4.75 mm, and divide it into two equal parts, randomly numbered as J1 and J2, each part of machine-made sand is 1500-2000g;

[0009] Step 2: Take J1 machine-made sand, irradiate it with electron beam, and then cool it for standby use;

[0010] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0011] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0012] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0013] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0014] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0015] The residual flocculant is a polyacrylamide or polyacrylamide / polyamine composite flocculant, the electron beam irradiation absorption dose is 30-40 kGy, and the flocculant mass concentration is the percentage of the flocculant mass to the mass of the machine-made sand after drying.

[0016] The critical moisture content test comprises the following steps:

[0017] Step 1: Place the sample in a metal tray and add deionized water accounting for 20% to 30% of the sample mass. Stir evenly and cover the surface with a film. Let it stand for 10-12 hours.

[0018] Step 2: Load the sample into the truncated cone test mold in three layers. The first layer is loaded to 3 / 10 of the truncated cone test mold, the second layer is loaded to 6 / 10 of the truncated cone test mold, and the third layer fills the truncated cone test mold. Each time the sample is loaded, it is evenly compacted 10-20 times with a metal cylindrical tamping rod. Each time the tamping rod is placed 20mm from the surface of the sample and allowed to fall freely. After the third layer is compacted, the sample is added in time to ensure that the test mold is completely filled.

[0019] Step 3: Remove the test mold vertically upwards. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over and use a hair dryer to blow the machine-made sand for 30s to 60s to evenly evaporate the moisture on the surface of the machine-made sand.

[0020] Step 4: Repeat step 2 until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0021] Step 5: Dry the sample in a 105°C oven until constant weight is reached. The critical moisture content η is calculated as follows:

[0022]

[0023] Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

[0024] The truncated cone test mold is made of one of polymethyl methacrylate and polycarbonate, with a thickness of 6 to 15 mm. The test mold is placed on a non-water-absorbent bottom plate for testing.

[0025] The truncated cone test mold is a transparent truncated cone test mold with scales, an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm.

[0026] The side slope of the frustum test mold is 5:1.

[0027] The diameter of the metal cylindrical tamping rod is 30 mm and the mass is 1000 g.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] (1) Residual flocculants in washed machine-made sand, such as polyacrylamide, will form hydrogen bonds with water to increase viscosity and thickening. Therefore, under the same water content conditions, machine-made sand containing flocculants has better "cohesiveness" and is easier to maintain its shape after compaction. In other words, the water content when the critical state defined in the present invention is reached is lower. Therefore, by comparing the difference in critical water content between untreated machine-made sand and machine-made sand after complete degradation, the content of residual flocculants can be more directly determined.

[0030] (2) Compared with the test of pure paste, mortar and concrete system, it avoids the deviation caused by introducing other materials and is more convenient, fast and accurate.

[0031] (3) Compared with conventional organic matter degradation treatment methods, electron beam radiation technology can be carried out under normal temperature and pressure conditions, and has the characteristics of high degradation efficiency, no need to add other chemical reagents, and no secondary pollution, thereby improving the accuracy of detection.

[0032] (4) Based on the stability of the sand accumulation state, a "critical water absorption rate" test method was proposed, and a transparent scaled round cone test mold was designed to accurately specify the filling height and compaction method of each layer of samples, thereby improving the standardization of tests at different times, locations, and by different operators. The side slope of the round cone test mold is 5:1, which is larger than the slope of the test mold in the relevant standard (4.4:1). The instability state of the machine-made sand sample is easier to observe, which can improve the objectivity and repeatability of judging the "critical state". BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 Schematic diagram of the transparent scaled frustum test mold and the cylindrical tamping rod in this embodiment. DETAILED DESCRIPTION

[0034] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. Figure 1 The relevant tests are carried out using the transparent scaled frustum test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm and a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g.

[0035] [Example 1]

[0036] Step 1: Screen out the particles larger than 4.75 mm from the artificial sand to be tested, and divide it into two equal parts, randomly numbered as J1 and J2, with each part of artificial sand weighing 1500 g.

[0037] Step 2: Take J1 machine-made sand, irradiate it with an electron beam, the electron beam irradiation absorbed dose is 30 kGy, and then cool it for use.

[0038] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0039] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0040] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0041] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0042] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0043] The critical moisture content test includes the following steps:

[0044] (1) Take 1500g of sample and put it into a metal tray. Add deionized water accounting for 20% of the sample mass, stir evenly, cover the surface with a film, and let it stand for 12 hours.

[0045] (2) The specimen is loaded into a transparent scaled truncated cone test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm in three layers. The first layer is loaded to scale 1, the second layer is loaded to scale 2, and the third layer fills the test mold. Each time the specimen is loaded, a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g is used to compact it evenly for 15 times. Each time the tamping rod is placed 20 mm from the surface of the specimen and allowed to fall freely. After the third layer is compacted, the specimen is added in time to ensure that the test mold is completely filled.

[0046] (3) Remove the test mold vertically upwards. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over, and use a hair dryer to blow the machine-made sand for 30 seconds to evenly evaporate the moisture on the surface of the machine-made sand.

[0047] (4) Repeat step (2) until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0048] (5) Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows:

[0049]

[0050] Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

[0051] The transparent test mold is made of polymethyl methacrylate with a thickness of 6 mm. The test mold is placed on a non-absorbent base for testing.

[0052] [Example 2]

[0053] Step 1: Screen out the particles larger than 4.75 mm from the artificial sand to be tested, and divide it into two equal parts, randomly numbered as J1 and J2, with each part of artificial sand weighing 2000 g.

[0054] Step 2: Take J1 machine-made sand, irradiate it with an electron beam, the electron beam irradiation absorbed dose is 40 kGy, and then cool it for use.

[0055] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0056] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0057] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0058] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0059] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0060] The critical moisture content test includes the following steps:

[0061] (1) Take 1500g of sample and put it into a metal tray. Add deionized water accounting for 30% of the sample mass, stir evenly, cover the surface with a film, and let it stand for 12 hours.

[0062] (2) The specimen is loaded into a transparent scaled truncated cone test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm in three layers. The first layer is loaded to scale 1, the second layer is loaded to scale 2, and the third layer fills the test mold. Each time the specimen is loaded, a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g is used to compact it evenly for 15 times. Each time the tamping rod is placed 20 mm from the surface of the specimen and allowed to fall freely. After the third layer is compacted, the specimen is added in time to ensure that the test mold is completely filled.

[0063] (3) Remove the test mold vertically upward. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over, and use a hair dryer to blow the machine-made sand for 60 seconds to evenly evaporate the moisture on the surface of the machine-made sand.

[0064] (4) Repeat step (2) until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0065] (5) Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows:

[0066]

[0067] Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

[0068] The transparent test mold is made of polycarbonate with a thickness of 15 mm. The test mold is placed on a non-absorbent base for testing.

[0069] [Example 3]

[0070] Step 1: Screen out the particles larger than 4.75 mm from the artificial sand to be tested, and divide it into two equal parts, randomly numbered as J1 and J2, with each part of artificial sand weighing 1750 g.

[0071] Step 2: Take J1 machine-made sand, irradiate it with an electron beam, the electron beam irradiation absorbed dose is 35 kGy, and then cool it for use.

[0072] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0073] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0074] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0075] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0076] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0077] The critical moisture content test includes the following steps:

[0078] (1) Take 1500g of sample and put it into a metal tray. Add deionized water accounting for 25% of the sample mass, stir evenly, cover the surface with a film, and let it stand for 12 hours.

[0079] (2) The specimen is loaded into a transparent scaled truncated cone test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm in three layers. The first layer is loaded to scale 1, the second layer is loaded to scale 2, and the third layer fills the test mold. Each time the specimen is loaded, a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g is used to compact it evenly for 15 times. Each time the tamping rod is placed 20 mm from the surface of the specimen and allowed to fall freely. After the third layer is compacted, the specimen is added in time to ensure that the test mold is completely filled.

[0080] (3) Remove the test mold vertically upward. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over, and use a hair dryer to blow the machine-made sand for 45 seconds to evenly evaporate the moisture on the surface of the machine-made sand.

[0081] (4) Repeat step (2) until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0082] (5) Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows:

[0083]

[0084] Among them, m 湿 is the critical state sample mass; m干 is the mass of the sample after drying.

[0085] The transparent test mold is made of polymethyl methacrylate with a thickness of 10 mm. The test mold is placed on a non-absorbent base for testing.

[0086] [Example 4]

[0087] Step 1: Screen out the particles larger than 4.75 mm from the artificial sand to be tested, and divide it into two equal parts, randomly numbered as J1 and J2, with each part of artificial sand weighing 1500 g.

[0088] Step 2: Take J1 machine-made sand, irradiate it with an electron beam, the electron beam irradiation absorbed dose is 40 kGy, and then cool it for use.

[0089] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0090] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0091] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0092] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0093] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0094] The critical moisture content test includes the following steps:

[0095] (1) Take 1500g of sample and put it into a metal tray. Add deionized water accounting for 30% of the sample mass. Stir evenly and cover the surface with a film. Let it stand for 12 hours.

[0096] (2) The specimen is loaded into a transparent scaled truncated cone test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm in three layers. The first layer is loaded to scale 1, the second layer is loaded to scale 2, and the third layer fills the test mold. Each time the specimen is loaded, a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g is used to compact it evenly for 15 times. Each time the tamping rod is placed 20 mm from the surface of the specimen and allowed to fall freely. After the third layer is compacted, the specimen is added in time to ensure that the test mold is completely filled.

[0097] (3) Remove the test mold vertically upward. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over, and use a hair dryer to blow the machine-made sand for 60 seconds to evenly evaporate the moisture on the surface of the machine-made sand.

[0098] (4) Repeat step (2) until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0099] (5) Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows:

[0100]

[0101] Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

[0102] The transparent test mold is made of polymethyl methacrylate with a thickness of 15 mm. The test mold is placed on a non-absorbent base for testing.

[0103] [Example 5]

[0104] Step 1: Screen out the particles larger than 4.75 mm from the artificial sand to be tested, and divide it into two equal parts, randomly numbered as J1 and J2, with each part of artificial sand weighing 2000 g.

[0105] Step 2: Take J1 machine-made sand, irradiate it with an electron beam, the electron beam irradiation absorbed dose is 30 kGy, and then cool it for use.

[0106] Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2):

[0107] When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%;

[0108] When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%;

[0109] When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%;

[0110] When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

[0111] The critical moisture content test includes the following steps:

[0112] (1) Take 1500g of sample and put it into a metal tray. Add deionized water accounting for 20% of the sample mass, stir evenly, cover the surface with a film, and let it stand for 12 hours.

[0113] (2) The specimen is loaded into a transparent scaled truncated cone test mold with an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm in three layers. The first layer is loaded to scale 1, the second layer is loaded to scale 2, and the third layer fills the test mold. Each time the specimen is loaded, a metal cylindrical tamping rod with a diameter of 30 mm and a mass of 1000 g is used to compact it evenly for 15 times. Each time the tamping rod is placed 20 mm from the surface of the specimen and allowed to fall freely. After the third layer is compacted, the specimen is added in time to ensure that the test mold is completely filled.

[0114] (3) Remove the test mold vertically upwards. If the sample can maintain its original shape, put the sample back into the tray, turn the sample over, and use a hair dryer to blow the machine-made sand for 30 seconds to evenly evaporate the moisture on the surface of the machine-made sand.

[0115] (4) Repeat step (2) until the sample can no longer maintain its original shape and particles are scattered on the surface.

[0116] (5) Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows:

[0117]

[0118] Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

[0119] The transparent test mold is made of polycarbonate with a thickness of 6 mm. The test mold is placed on a non-absorbent base for testing.

[0120] [Comparative Example 1]

[0121] The test method of Comparative Example 1 is basically the same as that of Example 1, except that the electron beam irradiation absorbed dose in step 2 is 20 kGy.

[0122] [Comparative Example 2]

[0123] The test method of Comparative Example 2 is basically the same as that of Example 1, except that: when testing the critical moisture content, the sample is turned over and the machine-made sand is blown by a hair dryer for 70 seconds each time.

[0124] Effect verification

[0125] Select the machine-made sand without flocculant produced by a machine-made sand factory, dilute the anionic polyacrylamide with a molecular weight of 14 million, add it to the machine-made sand according to the mass fraction of 0.007%, 0.03%, 0.06%, and 0.09% of the machine-made sand, and mix it evenly. Similarly, the anionic polyacrylamide with a molecular weight of 14 million and the polyamine flocculant are compounded in a ratio of 1:1 as a composite flocculant, and add it to the machine-made sand according to the mass fraction of 0.007%, 0.03%, 0.06%, and 0.09% of the machine-made sand and mix it evenly. The flocculant content in the machine-made sand is tested according to the method in Application Examples 1 to 5 and Comparative Examples 1 to 2, and the results are shown in Table 1 below.

[0126] Table 1 Flocculant content test results:

[0127]

[0128] As can be seen from Table 1, the detection method proposed in the present invention can accurately detect the content range of flocculants in machine-made sand, and has good accuracy and reliability. In Comparative Example 1, due to the small absorbed dose of electron beam irradiation, the residual flocculant was not completely degraded, so the difference in critical moisture content of the machine-made sand between the degradation treatment group and the untreated group was small, resulting in a small flocculant content detection result. In Comparative Example 2, when testing the critical moisture content, the sample was turned over and the machine-made sand was blown with a hair dryer for 70 seconds each time. Although the test result was accurate, the moisture content of the machine-made sand sample changed greatly due to the long blowing time. When judging the moisture content in the critical instability state, it is necessary to repeat it many times to achieve the state of "the sample just cannot maintain its original shape, and particles are scattered on the surface", which reduces the detection efficiency.

[0129] Although the present invention is described by way of embodiments, the embodiments are not intended to limit the present invention. Those skilled in the art may make various modifications and improvements within the spirit of the present invention, such as adjustment of the composition ratio or time range, and the effect after such adjustment is predictable, so it is also within the protection scope of the present invention. Therefore, the protection scope of the present invention shall be based on the protection scope defined by the same or equivalent technical features of the claims of this application.

Claims

1. A rapid detection method for residual flocculant content in water-washed machine-made sand, characterized in that: The following steps are involved: Step 1: Screen the machine-made sand to be tested to remove particles larger than 4.75 mm, and divide it into two equal parts, randomly numbered as J1 and J2, each part of machine-made sand is 1500-2000g; Step 2: Take J1 machine-made sand, irradiate it with electron beam, and then cool it for standby use; Step 3: Test the critical moisture contents η1 and η2 of the processed J1 and unprocessed J2 machine-made sands respectively, and determine the mass concentration of the flocculant based on the difference in the critical moisture contents of the two machine-made sands (η1-η2): When (η1-η2)≤0.2%, the mass concentration of flocculant is ≤0.01%; When 0.2%<(η1-η2)≤1.0%, 0.01%<mass concentration of flocculant≤0.05%; When 1.0%<(η1-η2)≤2.0%, 0.05%<mass concentration of flocculant≤0.08%; When 2.0%<(η1-η2), 0.08%<mass concentration of flocculant.

2. A rapid detection method for residual flocculant content in water-washed machine-made sand according to claim 1, characterized in that: The residual flocculant is a polyacrylamide or polyacrylamide / polyamine composite flocculant, the electron beam irradiation absorption dose is 30-40 kGy, and the flocculant mass concentration is the percentage of the flocculant mass to the mass of the machine-made sand after drying.

3. The method for rapid detection of residual flocculant content in water-washed machine-made sand according to claim 1 is characterized in that: The critical moisture content test comprises the following steps: Step 1: Place the sample in a metal tray and add deionized water accounting for 20% to 30% of the sample mass. Stir evenly and cover the surface with a film. Let it stand for 10-12 hours. Step 2: Load the sample into the truncated cone test mold in three layers. The first layer is loaded to 3 / 10 of the truncated cone test mold, the second layer is loaded to 6 / 10 of the truncated cone test mold, and the third layer fills the truncated cone test mold. Each time the sample is loaded, it is evenly compacted 10-20 times with a metal cylindrical tamping rod. Each time the tamping rod is placed 20mm from the surface of the sample and allowed to fall freely. After the third layer is compacted, the sample is added in time to ensure that the test mold is completely filled. Step 3: Remove the test mold vertically upwards. If the sample can maintain its original shape, put the sample back into the metal tray, turn the sample over and use a hair dryer to blow the machine-made sand for 30s to 60s to evaporate the moisture on the surface of the machine-made sand evenly. Step 4: Repeat step 2 until the sample just cannot maintain its original shape and particles are scattered on the surface; Step 5: Place the sample in a 105°C oven and dry it to constant weight. The critical moisture content η is calculated as follows: Among them, m 湿 is the critical state sample mass; m 干 is the mass of the sample after drying.

4. The method for rapid detection of residual flocculant content in water-washed machine-made sand according to claim 3 is characterized by: The truncated cone test mold is made of one of polymethyl methacrylate and polycarbonate, with a thickness of 6 to 15 mm. The test mold is placed on a non-water-absorbent bottom plate for testing.

5. A rapid detection method for residual flocculant content in water-washed machine-made sand according to claim 3 or 4, characterized in that: The truncated cone test mold is a transparent truncated cone test mold with scales, an upper inner diameter of 60 mm, a lower inner diameter of 100 mm, and a height of 100 mm.

6. A rapid detection method for residual flocculant content in water-washed machine-made sand according to claim 3 or 4, characterized in that: The side slope of the frustum test mold is 5:

1.

7. The method for rapid detection of residual flocculant content in water-washed machine-made sand according to claim 3 is characterized by: The diameter of the metal cylindrical tamping rod is 30 mm and the mass is 1000 g.

Citation Information

Patent Citations

  • Method for rapidly detecting residual quantity of flocculating agent in sand for concrete

    CN113720804A

  • Method for testing content of flocculant in machine-made sand

    CN117664794A

Cited By

  • Detection method for rapidly determining flocculant residue in washed sand

    CN120214279A

  • A method for rapidly determining the presence of flocculant residues in water-washed sand

    CN120214279B

  • Method for rapidly detecting residual quantity of polyacrylamide in machine-made sand

    CN122259552A